Calcium-fortified pandesal development and calcium availability - Malibiran, Claire Santos (2003)
ABSTRACT Calcium nutrition is linked to bone health and is a risk factor to osteoporosis. Special concern is given to the low intake of calcium-rich foods during crucial years of peak bone mass development at ages 9-18 years. There is a need to increase daily intake of calcium. Pandesal, a usual breakfast and snack food of every Filipino, is a good vehicle to fortify with calcium. The main objective of this study is to develop a calcium-fortified pandesal and to assess the effectiveness of the fortification through determination of the dialyzable calcium as a measure of calcium availability. Pandesal was fortified with calcium lactate to meet 33% of the Recommended Daily Allowances among Filipinos 11-24 years of age. Development of the calcium-fortified pandesal was achieved through: assessment of the reproducibility of the basic formulation; modification of the basic formulation to produce highly acceptable calcium-fortified pandesal; and characterization of the pandesal. Calcium availability of fortified and unfortified pandesal was determined using an in vitro method simulating conditions that prevail in the stomach and small intestine. Results showed that the basic formulation was not reproducible and needed improvement. Pandesal produced from the modified formulation did not differ significantly from the unfortified and the original pandesal in terms of acceptability and physical characteristics. However, calcium content and availability varied between the fortified and the control pandesal. Results of in vitro evaluation (CV=0.35-1.68%) showed that 1.457 mg of calcium was potentially available from every gram of fortified pandesal containing 3.369mg of calcium. In conclusion, producing an acceptable calcium-fortifed pandesal is possible using the developed formulation. Considering the bioavailability of calcium in the fortified pandesal, a 40-gram serving portion meets 8.4% of the RDA (700mg calcium) for the target group.